PENGARUH FIXED ASSETS TURNOVER, QUICK RATIO DAN TIMES INTEREST EARNED TERHADAP RETURN ON ASSET PADA PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Victor Erlian; Holfian Daulat Tambun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
In develoving national economy, property sector has an important role. This sector is as strategic as other sectors, such as agriculture, industry, trade, services, and others. Property with a focus in the field of housing and construction is one of the sectors absorbing large amounts of labor and the multiplier effect is quite long. Therefore, this sector has big effect to support the development of economy sectors. This research aims at testing and analyzing the effect of Fixed Assets Turnover, Quick Ratio, and Times Interest Earned on Return On Asset on sub-sector company of property and real estate registered on Indonesia Stock Exchange in 2013-2017 period. Data analyzing was done by Software SPSS 22. Method of data analysis used is descriptive statistics, classic assumption test, multiple linear regression analysis and hypothesis testing (partial test, simultaneous test and coefficient of determination). The results of the study prove that each (partial) shows that Fixed Assets Turnover has no significant effect. Quick Ratio has no significant effect. Times Interest Earned has a positive and significant effect. Simultaneously, the variables Fixed Assets Turnover, Quick Ratio, and Times Interest Earned have a positive and significant effect on Return On Assets, with a coefficient of determination of 59.2%. The remaining 40.8% is the influence of the variables described outside in this study.